Enhanced neutrophil response in chronic obstructive pulmonary disease. Issue 6 (1st June 2001) - Noguera, A; Batle, S; Miralles, C; Iglesias, J; Busquets, X; MacNee, W; Agustí, A G N
Abstract : BACKGROUND: Neutrophils are likely to play a major role in the inflammatory response seen in chronic obstructive pulmonary disease (COPD). This study sought to address the hypothesis that an enhanced neutrophil response to proinflammatory agents in COPD may contribute to their recruitment and activation in the lungs. METHODS: Circulating neutrophils were obtained from 10 patients with COPD, eight long term smokers with normal lung function, and eight healthy never smoking controls. The in vitro production of reactive oxygen species (ROS) was measured by the NADPH oxidase method (respiratory burst) and the surface expression of several adhesion molecules (Mac-1, LFA-1 andl -selectin) was measured by flow cytometry. Measurements were obtained under basal conditions and after stimulation with phorbol myristate acetate (PMA) and tumour necrosis factor alpha (TNFα). mRNA levels of p22- phox (a subunit of NADPH oxidase) and Mac-1 (CD11b) were also determined by reverse transcriptase polymerase chain reaction (RT-PCR). RESULTS: Patients with COPD showed enhanced respiratory burst compared with smokers with normal lung function, both under basal conditions (mean (SE) fluorescence intensity (MFI) 15.1 (0.5) v 11.6 (0.5); mean difference –3.4 (95% CI of the difference –5.1 to –1.8), p<0.01) and after PMA stimulation (MFI 210 (7) v 133 (10); mean difference –77 (95% CI of the difference –102 to –52), p<0.01). Mac-1 surface expression was also enhanced in patients with COPD, both under basal conditions (MFI 91 (5) v 45 (3); mean difference –46 (95% CI of the difference –61 to –31), p<0.001) and after stimulation with TNFα (MFI 340 (15) v 263 (11); mean difference –77 (95% CI of the difference –119 to –34), p=0.001). These differences were also apparent when patients with COPD were compared with non-smokers (p<0.05). The mRNA levels of p22- phox and Mac-1 (CD11b) were similar in patients with COPD and smokers with normal lung function, suggesting that the observed differences were due to post-transcriptional regulation. CONCLUSIONS: These results demonstrate an enhanced neutrophil response to proinflammatory agents in patients with COPD which may contribute to their enhanced recruitment and activation in the lungs of these patients. These findings support those of other studies which have indicated that the neutrophil is likely to play a major role in the pathogenesis of this disease.